EVALUATION OF POLIO IMMUNIZATION COVERAGE AND ACUTE FLACCID PARALYSIS SURVEILLANCE IN EAST JAVA, INDONESIA, 2018-2022 - Abubakar Tarawally; Arief Hargono; Hugeng Susanto; Wahyu Wulandari (Universitas Airlangga, 2024)
Background: Indonesia has successfully eradicated wild poliovirus since 2005 using robust immunization and AFP surveillance programs. However, circulating vaccine-derived poliovirus type 2 has challenged these commitments, followed by the 2024 outbreak in East Java. Purpose: The study aims to analyze the polio eradication initiative by assessing polio immunization coverage and AFP surveillance in East Java. Methods: A descriptive, quantitative study design and retrospective analysis of polio immunization coverage and AFP surveillance indicators from the Provincial Health Office, East Java, from 2018-2022. The data was collected and analyzed using Excel, EpiInfo7, and Health Mapper software. Results: OPV4 coverage ranged from 89.95% to 100.76%, while IPV coverage ranged from 73.98 % to 94.18% from 2018 to 2020; the proportion of districts and cities for IPV coverage increased from 0% in 2018 to 44.74% in 2022, below the 95% WHO target. Of the 826 cases of AFP reported, 820 (99.27%) were actual AFP cases <15 years of age, with most (49.02%) being <5 years of age. Non-polio AFP rates ranged from 0.80 in 2020 to 2.59 in 2022 per 100,1000 <15 years of age, with the proportion of districts and cities slightly declining from 55.26% in 2018 to 50% in 2022. The annual mean percentage of AFP-adequate specimens is 61.15%, with the proportion of districts and cities significantly declining from 31.58% in 2018 to 10.53% in 2022, below the 80% target. Conclusion: IPV immunization coverage and AFP surveillance indicators are below the WHO-recommended targets across districts and cities in East Java.